Voice analysis before and after vocal rehabilitation in patients following open surgery on vocal cords - Bunijevac, Mila B; Petrović-Lazić, Mirjana; Jovanović-Simić, Nadica; Vuković, Mile (Vojnosanitetski pregled, 2017)
Background/Aim. The major role of larynx in speech, respiration and swallowing makes carcinomas of this region and their treatment very influential for patients’ life quality. The aim of this study was to assess the importance of voice therapy in patients after open surgery on vocal cords. Methods. This study included 21 male patients and the control group of 19 subjects. The vowel (A) was recorded and analyzed for each examinee. All the patients were recorded twice: firstly, when they contacted the clinic and secondly, after a three-month vocal therapy, which was held twice per week on an outpatient basis. The voice analysis was carried out in the Ear, Nose and Throat (ENT) Clinic, Clinical Hospital Center “Zvezdara” in Belgrade. Results. The values of the acoustic parameters in the patients submitted to open surgery on the vocal cords before vocal rehabilitation and the control group subjects were significantly different in all specified parameters. These results suggest that the voice of the patients was damaged before vocal rehabilitation. The results of the acoustic parameters of the vowel (A) before and after vocal rehabilitation of the patients with open surgery on vocal cords were statistically significantly different. Among the parameters – Jitter (%), Shimmer (%) – the observed difference was highly statistically significant (p < 0.01). The voice turbulence index and the noise/harmonic ratio were also notably improved, and the observed difference was statistically significant (p < 0.05). The analysis of the tremor intensity index showed no significant improvement and the observed difference was not statistically significant (p > 0.05 ). Conclusion. There was a significant improvement of the acoustic parameters of the vowel (A) in the study subjects three months following vocal therapy. Only one out of five representative parameters showed no significant improvement.
Keywords: otorhinolaryngologic surgical procedures; laryngeal neoplasms; treatment outcome; voice quality; rehabilitation; speech production measurement